Analysis of Power Transformer Oil Insulation Capability Against Breakdown Voltage Due to Temperature and Loading - Gea, Daniman; Gunawan, Haris; Lesmana, Dicky (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2025)
The reliability of power transformers heavily depends on the performance of insulating oil, which serves as both an electrical insulation medium and a cooling agent. One of the key factors in maintaining the quality of insulating oil is its breakdown voltage, which determines the oil's ability to withstand electrical stress before insulation failure occurs. The rise in temperature during transformer operation can lead to a decrease in the oil's breakdown voltage, thus affecting the overall reliability of the transformer. This study aims to analyze the effect of temperature rise on the breakdown voltage of power transformer oil. Testing was conducted through simulations and laboratory measurements at various temperatures to identify the relationship between temperature and the oil's breakdown voltage. The results of the study indicate that an increase in temperature significantly reduces the breakdown voltage of insulating oil, thereby increasing the risk of insulation failure and reducing transformer reliability. The conclusions of this study provide essential recommendations for managing transformer operating temperatures to maintain optimal reliability and service life while avoiding potential failures caused by insulating oil degradation.